Covid-19 pandemic and its impact on medical students in Maceió, Alagoas, Northeast Brazil (Research, Society and Development, 2022)
Objective: To evaluate the impact generated by the Covid-19 pandemic on the lives of medical students in Alagoas, in addition to investigating the level of knowledge of students in relation to the pandemic generated by the new coronavirus. Methods: This was a descriptive and transversal research, which used the electronic means (WhatsApp) to send the questionnaires to the students, containing questions related to mental and physical health and knowledge about the coronavirus. The study was approved by the Research Ethics Committee. Results: 243 students answered the survey from the State of Alagoas, distributed in the four medical teaching institutions of the capital. There were reports of negative changes in sleep, food, concentration during the pandemic period. Only 10 (4.11%) students reported not having anxiety and only 7 (2.9%) said they were not worried about the pandemic. It was also noticed that despite the predominant negative feelings, the students claimed to have knowledge about the new coronavirus and are up to date on the virus. Conclusion: the negative feelings generated during the pandemic can contribute negatively to medical training, requiring such faculties to reflect on the training of doctors in Alagoas.